Reliability of Posttherapeutic Dosimetry of Patients with Short-term Hospitalisation after Radioiodine Therapy - Körber, C.; Schneider, P.; Hänscheid, H.; Köck, P. R.; Reiners, Chr. (Nuklearmedizin - NuclearMedicine, 2000)
Aim: According to the new recommendations of the Federal German Radiation Protection Committee (SSK) for patient discharge, that were published in April 1997, patients can be discharged after radioiodine therapy with a radiation exposure of less than 1 mSv per year in 2 m distance. The aim of this study was to evaluate whether the measurement of the achieved dose was different 48 hours after application of I-131 and after an interval of one week. The study was planned in order to ensure quality management in the follow-up of the patients. Method: In a prospective study 115 patients were followed, that were treated for a benign thyroid disease. The patients were discharged 48 hours after the intake of I-131 after falling short of the exposure limit. All patients were measured at discharge and about 8 days later with the same uptake facility. Results: Because of similar results focal and disseminated forms of benign thyroid diseases could be analysed together. The calculated doses 8 days after the discharge were higher than the values at the time of discharge. The doses were underestimated about 4% with an standard error of 15%. Conclusion: The error in early dosimetric measurements is small in comparison to the overall uncertainty in therapy and uptake dosimetry. A valid dosimetry and sufficient quality management can be guaranteed even for an early discharge.
Keywords: Iodine-131; radioiodine therapy; dosimetry; benign thyroid disease; radiation protection